Management Strategy for Community Zakat Fund Collection for Sustainable Human Prosperity and Well-Being in Singapore - Bayumi, Muhamad Rahman; Diem, M. Junestrada; Jaya, Rizal Alfit; Wibisono, Eristian (Yayasan Riset dan Pengembangan Intelektual, 2025)
Strategic management in the management of zakat in Singapore has provided a leading breakthrough in encouraging minimal risks from community fund management. Practices that are far from corruption, collusion and nepotism make the fund management institution an institution that is worthy of being adopted. Good zakat fund collection has been proven to have a positive influence on increasing zakat collections in Singapore in the sector of the availability of social services, education facilities, health and employment for the Muslim community. Singapore as the only developed country in Southeast Asia is very appropriate to be a pilot country in various aspects of zakat fund management. This study aims to explore and describe the practice of zakat fund management in Singapore. This study was designed with a qualitative approach. Data were collected through interviews, interviews and observations. The data analysis technique used Miles Huberman with the stages of data collection, data reduction, presentation and drawing conclusions. The findings of this study provide extensive learning about comprehensive zakat fund management that is beneficial for any institution or country in achieving sustainable prosperity and prosperity. This study provides several recommendations for countries and institutions managing community funds in achieving sustainable prosperity and welfare goals.